Falling Utilization Factor of Thermal Power Plants in India and Its Financial Impact - Tripathi, Alok K.; Anand, Neeraj (International Journal of Energy Economics and Policy, 2022)
Thermal power plants in India are operating under very low Utilization Factors. The average national Utilization Factor of coal based thermal power plants was 77.5 % % in 2009-10 which has come down to 53.37 % in 2021-22. Many studies and reports indicate that, in the business-as-usual situation, average Utilization Factor may drop to 40% in next 2-3 years. This situation has arisen partly because of substantial injection of renewable energy in the grid. Since the renewable energy provides intermittent supply, thermal plants have to dance to the tune of renewable energy in order to sustain the grid stability. These thermal plants have to therefore ramp-up and ramp-down load several times a day. It is one of the major causes for overall low Utilization Factor. The situation is now putting immense technical and financial pressure on the thermal plants. Regulators, policy makers, power plant developers, lenders and other key stakeholders need to take notice of it. In this paper, we explore the direct financial impact on the Profits / Return on Equity (ROE) of thermal power plants under these circumstances. We find that under the regulated tariff regime, thermal power plants may see a reduction in Return on Equity (ROE) to the tune of 26 % if average Utilization Factor drops from a level of 90 % to 35 %.